Characterization of the semen, gut, and urine microbiota in patients with different semen abnormalities - Cao, Tingshuai; Wang, Shangren; Pan, Yang; Guo, Feng; Wu, Bin; Zhang, Yingchun; Wang, Yujie; Tian, Jiaqing; Xing, Qingfei; Liu, Xiaoqiang (Frontiers in Microbiology, 2023)
Introduction: Semen quality is decreasing worldwide, leading to increased male infertility. This study analyzed the microbiota of the gut, semen, and urine in individuals with semen abnormalities to identify potential probiotics and pathogenic bacteria that affect semen parameters and help develop new methods for the diagnosis and treatment of patients with semen abnormalities. Methods: We recruited 12 individuals with normal semen parameters (control group), 12 with asthenospermia but no semen hyperviscosity (Group_1), 6 with oligospermia (Group_2), 9 with severe oligospermia or azoospermia (Group_3), and 14 with semen hyperviscosity only (Group_4). The semen, gut, and urine microbiota were examined by analyzing the 16S ribosomal RNA gene sequence using next-generation sequencing. Results: The gut microbes were clustered into the highest number of operational taxonomic units, followed by urine and semen. Furthermore, the α-diversity of gut microbes was highest and significantly different from that of urine and semen microbiota. The microbiota of the gut, urine, and semen were all significantly different from each other in terms of β-diversity. The gut abundance of Collinsella was significantly reduced in groups 1, 3, and 4. Furthermore, the gut abundance of Bifidobacterium and Blautia was significantly decreased in Group_1, while that of Bacteroides was significantly increased in Group_3. The abundance of Staphylococcus was significantly increased in the semen of groups 1 and 4. Finally, Lactobacillus abundance was significantly reduced in the urine of groups 2 and 4. Discussion: This study comprehensively describes the differences in intestinal and genitourinary tract microbiota between healthy individuals and those with abnormal semen parameters. Furthermore, our study identified Collinsella, Bifidobacterium, Blautia, and Lactobacillus as potential probiotics. Finally, the study identified Bacteroides in the gut and Staphylococcus in semen as potential pathogenic bacteria. Our study lays the foundation of a new approach to the diagnosis and treatment of male infertility.